2021
DOI: 10.1080/10447318.2021.1921365
|View full text |Cite
|
Sign up to set email alerts
|

User Requirements for Inclusive Technology for Older Adults

Abstract: Active aging technologies are increasingly designed to support an active lifestyle. However, the way in which they are designed can raise different barriers to acceptance of and use by older adults. Their designers can adopt a negative stereotype of aging. Thorough understanding of user requirements is central to this problem. This paper investigates user requirements for technologies that encourage an active lifestyle and provide older people with the means to self-manage their physical, mental, and emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Thus, hospital-to-home interventions seeking to incorporate digital technologies should consider the intersection between disability and age and offer training and practice for the implemented technology [ 132 ]. Future research should explore ways to meet the needs of older adults with various impairments by designing technology that is as inclusive as possible [ 133 ]. In efforts to reduce inequities related to age and disability, strategies such as including individuals with disabilities (eg, dementia [ 134 ]) in technological development have been used [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hospital-to-home interventions seeking to incorporate digital technologies should consider the intersection between disability and age and offer training and practice for the implemented technology [ 132 ]. Future research should explore ways to meet the needs of older adults with various impairments by designing technology that is as inclusive as possible [ 133 ]. In efforts to reduce inequities related to age and disability, strategies such as including individuals with disabilities (eg, dementia [ 134 ]) in technological development have been used [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning technology design, the objective is to find cost-effective solutions to help independent living and provide health care and well-being [10]. A comprehensive analysis of information and communication technology research and development revealed the common goals of these technologies as the provision of health, accessibility, and safety [11,12]. Many technologies seek to assist older adults with everyday activities [4,11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis of information and communication technology research and development revealed the common goals of these technologies as the provision of health, accessibility, and safety [11,12]. Many technologies seek to assist older adults with everyday activities [4,11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Other identified factors that support independent living are to facilitate socialisation, communication, and to consider eHealth user's safety [2,11,41]. The study by [13], recommends that eHealth services should be implemented with the aim to strengthen older adults' mobility and self-management.…”
Section: Findings and Discussionmentioning
confidence: 99%